New synthetic fiber armored cable for freezing-in thermal ice probes. Issue 85 (3rd September 2021) - Zhang, Nan; Liu, Hui; Talalay, Pavel; Sun, Youhong; Li, Na; Fan, Xiaopeng; Li, Bing; Gong, Da; Hong, Jialin; Wang, Ting; Liu, An; Li, Yazhou; et al.
Abstract: A series of new synthetic armored cables were developed and tested to ensure that they were suitable for use with the RECoverable Autonomous Sonde (RECAS), which is a newly designed freezing-in thermal ice probe. The final version of the cable consists of two concentric conductors that can be used as the power and signal lines. Two polyfluoroalkoxy jackets are used for electrical insulation (one for insulation between conductors, and the other for insulation of the outer conductor). The outer insulation layer is coated by polyurethane jacket to seal the connections between the cable and electrical units. The 0.65 mm thick strength member is made from aramid fibers woven together. To hold these aramid fibers in place, a sheathing layer was produced from a polyamide fabric cover net. The outer diameter of the final version of the cable is 6.1 mm. The permissible bending radius is as low as 17–20 mm. The maximal breaking force under straight tension is 12.2 kN. The cable weight is only 0.061 kg m −1 . The mechanical and electrical properties and environmental suitability of the cable were determined through laboratory testing and joint testing with the probe.